Human Resource Management in Islamic Education: Evolution, Approaches, and Challenges - Bilqis Auliatul Khamima; Erica Wahyu Izzati; Mardiyah Mardiyah; Fauzia Rosalia Trisnia (UIN Siber Syekh Nurjati Cirebon, 2025)
Human resource (HR) management is a crucial factor in improving the quality of Islamic education, as the quality of teachers, educational staff, and students significantly determines the success of an institution. Human Resource Management (HRM) presents itself as a modern approach that positions people as strategic assets, in contrast to traditional personnel management, which tends to be administrative. This study aims to understand the concept of HRM, trace its development, and examine the approaches and challenges of its implementation in Islamic education. Using a descriptive-qualitative method through a literature review, this study confirms that HRM encompasses the functions of planning, recruitment, development, performance assessment, and HR welfare. HRM is developing rapidly in developing countries thanks to technological support, while in developing countries it still faces limitations. There are five main approaches: mechanical, paternalistic, systems, humanistic, and contingency. Challenges to Islamic education include globalization, digitalization, and social dynamics. HRM plays a strategic role in building professional, adaptive, innovative, and Islamically valued Islamic education.